Requirement analysis for the design of smart logistics in SMEs - Patrick Dallasega (2020)
© The Author(s) 2020. Based on expert interviews and case studies, the authors investigate requirements for small-and medium-sized enterprises (SMEs) to support logistics management with Industry 4.0 concepts, in the context of mass customization and global supply chain challenges. In an exploratory field study, specific requirements of SMEs from Europe, the United States of America, and Thailand to use Industry 4.0 concepts in their logistics management are analyzed. By using Axiomatic Design, customer needs for the design of smart and intelligent logistic systems can be translated into a hierarchy of functional requirements and corresponding physical solutions while maintaining functional independence and minimizing information content. The determined functional requirements are used as a basis to define design guidelines for suitable Industry 4.0 concepts to support the logistics management process.